Thermomechanical Wear Testing of Metal Matrix Composite Cladding for Potential Application in Hot Rolling Mills. Issue 5 (2nd December 2019) - Domitner, Josef; Aigner, Michael; Stern, Thomas; Paar, Armin; Sommitsch, Christof; Elizondo, Leonel
Abstract : Laser metal deposition (LMD) is utilized to clad the surface of a miniaturized test roll (Ø 40 mm) of tool steel. The cladding consists of two layers: a nickel alloy as intermediate layer deposited onto the surface of the steel substrate, and a metal matrix composite (MMC) as top layer consisting of spherical tungsten carbide particles embedded into the nickel alloy matrix. The thermomechanical wear behavior of the cladding is investigated on a test rig, where the test roll is pressed against an inductively heated load roll. Multiple test runs up to several hours simulating industrial loading conditions are performed. The presented testing procedure enables predicting the time‐dependent abrasive wear behavior of the cladding, in particular for hot rolling mill applications. After testing for 8 h at temperature of 650 °C and at contact pressure of approximately 1 GPa, the maximum depth of the wear mark is about 0.12 mm. Partial cracking, debonding and dissolution of the tungsten carbide particles, as well as formation of iron and chromium oxides at the surface of the wear marks occur. However, as low abrasive wear is observed, the investigated MMC may potentially be applicable for cladding rolls in steel hot rolling mills. Abstract : The potential of a metal matrix composite (MMC) for hard‐facing steel rolls used in hot rolling mills and operated at harsh thermomechanical load conditions is investigated. The microstructure of this MMC consists of hard tungsten carbide particles embedded in a comparatively soft nickel alloy matrix. The MMC is produced by powder‐based laser cladding. The energy dispersive X‐ray (EDX) element maps illustrate the distributions of tungsten (orange) and nickel (yellow) inside the particles and inside the matrix, respectively.